Serotonin transporter gene (5-HTT) polymorphism and major depressive disorder in patients in bogotá, Colombia (2016)
Introduction: The 5-HTT short allele has been controversially associated with an increased risk of major depressive disorder. Objective: To determine the association of 5-HTT short allele with major depression in Bogotá, Colombia. Materials and methods: We carried out a study of cases (n=68) matched 1:1 with controls by gender and age (±5 years). Major depression was diagnosed using the Mini-International Neuropsychiatric Interview, and 5-HTT polymorphism using PCR. Results: Females were predominant (82.4%). The S (short) allele predominated in cases compared with controls (S: 72.1% vs. 63.2; L (long): 27.9% vs. 36.8%), and the SL genotype was more frequent in cases (SL: 45.6% vs. 36.8%; LL: 27.9% vs. 36.8%; SS: 26.5% vs. 26.5%), although not significantly. There were significant differences in those under age 37, with a predominance of the S allele in cases (p=0.038; OR=2.75; 95% CI: 0.88-8.64). Multivariate analysis, adjusted for comorbid anxiety disorders, showed a significant association of major depression with the SL genotype (p=0.049; OR=3.20; 95% CI: 1.00-10.23); the S allele was close to statistical significance (p=0.063; OR=2.94; 95% CI: 0.94-9.13), and it was statistically significant in cases under 37 years of age (p=0.026; OR=10.79; 95% CI: 1.32-80.36). Conclusions: The SL genotype was associated with major depressive disorder in patients of all ages. The S allele was significantly associated with major depressive disorder in patients under age 37, adjusted for comorbid anxiety disorders.